Implementasi algoritma brute force dalam pencarian menu pada aplikasi pemesanan coffee - Ramadani, Moh Roghil Affan (Maliki Interdisciplinary Journal, 2025)
This paper discusses the implementation of the Brute Force algorithm in menu searching for a coffee ordering application. The Brute Force algorithm operates by sequentially examining all possible characters until the desired match is found. The main focus of this research is to analyze the effectiveness of the Brute Force algorithm in the context of applications with relatively small menu data. The results show that this algorithm is easy to implement and fairly efficient for limited data. However, for applications with larger datasets, it becomes less optimal and requires alternatives such as Binary Search or Hashing algorithms. This paper is expected to assist application developers in designing more user-friendly and efficient search systems.